2019
DOI: 10.1016/j.ejca.2019.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Sentinel lymph node detection in High-Risk Endometrial Cancer (SHREC-trial)—the final step towards a paradigm shift in surgical staging

Abstract: Study aims: To prospectively assess the diagnostic accuracy of a pelvic sentinel lymph node (SLN) algorithm in high-risk endometrial cancer (HREC). Patients and methods: Consecutive women with presumed FIGO stage I-II HREC underwent robotic surgery at two academic centres by five accredited surgeons. An anatomically based algorithm was adhered to, following cervical injection of indocyanine green (ICG), with reinjection of tracer in case of non-display of predefined lymphatic pathways. After removal of SLNs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
171
5
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(211 citation statements)
references
References 30 publications
20
171
5
15
Order By: Relevance
“…Recently published data using SLN in high-risk endometrial cancer found cervical injection accurate for pelvic mapping (NPV 99%). However, after aortic lymphadenectomy, more than 40% of node-positive patients also had positive aortic nodes, which were not SLNs 22 25. In our series, almost half the patients with nodal involvement had aortic metastases.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Recently published data using SLN in high-risk endometrial cancer found cervical injection accurate for pelvic mapping (NPV 99%). However, after aortic lymphadenectomy, more than 40% of node-positive patients also had positive aortic nodes, which were not SLNs 22 25. In our series, almost half the patients with nodal involvement had aortic metastases.…”
Section: Discussioncontrasting
confidence: 46%
“…Geppert et al21 studying lymphatic anatomy found a 47% SLN detection rate in the aortic area after fundal injection of ICG (following the infundibolopelvic pathway). However, the same group, in a recent study (SHREC-trial) analyzing pelvic SLN detection in high-risk endometrial cancers after cervical injection of ICG, found no migrations via the infundibolopelvic pathway nor the inframesenteric SLNs (“that would have required the absence of nodes along the pelvic pathways”) 22. A clear definition on SLNs is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the SHREC study no complications associated with the SLN procedure were observed, indicating the importance of surgical experience. Another study performed at our institution showed a 13-fold decrease in symptomatic lower limb lymphedema (18.1% compared with 1.3%) and a 5-fold decrease in the incidence of pelvic lymphoceles (13.3% compared with 2.6%) after SLN only compared with a full pelvic lymph node dissection, demonstrating the potential of the SLN concept in decreasing postoperative lymphatic complications 2 11 13 14…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, the principle of a full site-specific lymphadenectomy in case of non-mapping may be questioned from a morbidity perspective, particularly in low risk endometrial cancer patients. The additional 30 min required in the Pelvic SLN detection in the High-Risk Endometrial Cancer (SHREC) study for the SLN procedure, where dissection along both the upper and lower paracervical pathways were performed, is likely too time-consuming to motivate a similar SLN algorithm in presumed low-risk patients, taking into account that surgeries were performed by a few well experienced surgeons 2 11 13. On the other hand, in the SHREC study no complications associated with the SLN procedure were observed, indicating the importance of surgical experience.…”
Section: Introductionmentioning
confidence: 99%
“…Our study confirmed that the incidence of nodal metastases increased from 13% in the group of patients submitted to standard lymphadenectomy to 25% in the group of patients who underwent SLN biopsy. Furthermore, even if prospective data are needed to verify the reliability and the applicability of this SLN strategy in routine practice over standard lymphadenectomy in high-risk subgroups of women,15–17 there is also new evidence of promising results in this subgroup of patients with apparently confined endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%